A Survey on Homomorphic Encryption in Cloud Security - C.R, Kavitha; Harsoor, Bharati (International Journal of Engineering and Technology, 2018)
An outsourcing of data is increasing the data storage in Cloud. These raise numerous new challenges of privacy concern for persons and business. Sending data in the encrypted form to the cloud is a common approach to handle the privacy concern. Homomorphic Encryption technique is used to carry out significant computations on the data in the cloud. Random computations over ciphertext are allowed in Fully Homomorphic Encryption. Many solutions using fully homomorphic encryption have been proposed and also many researchers have tried to improve, proving efficiency is very hard. In this paper, Delegated Parallel Homomorphic Encryption is proposed. Also, an analysis has been made to exhibit various applications in the real world. The system must work efficiently without compromising the required cloud security services.Â Â